1990
DOI: 10.1002/job.4030110506
|View full text |Cite
|
Sign up to set email alerts
|

New hire perceptions of their own and their employer's obligations: A study of psychological contracts

Abstract: SummaryPsychological contracts are individual beliefs in reciprocal obligations between employees and employers. In a sample of 224 graduating MBA students who had recently accepted job offers, beliefs regarding employment obligations were investigated. Two types of obligation were demonstrated empirically: transactional obligations of high pay and career advancement in exchange for hard work and relational obligations exchanging job security for loyalty and a minimum length of stay. These types of obligations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

37
1,310
3
125

Year Published

1994
1994
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 1,375 publications
(1,475 citation statements)
references
References 12 publications
37
1,310
3
125
Order By: Relevance
“…These items capture aspects of the employment relationship studied in the majority of previous research (Robinson, 1996;Rousseau, 1990;Turnley & Feldman, 1999) such as pay, job security and career prospects.…”
Section: Methodsmentioning
confidence: 99%
“…These items capture aspects of the employment relationship studied in the majority of previous research (Robinson, 1996;Rousseau, 1990;Turnley & Feldman, 1999) such as pay, job security and career prospects.…”
Section: Methodsmentioning
confidence: 99%
“…the implied contract of continued future employment) and that an employee's performance is perceived as a consideration (a way of paying for the promise). Rousseau (1990), examining the emergence of psychological contracts in a survey of newly recruited MBAs, found that employees developed psychological contracts during the recruitment process. The content of that contract was related to what type of relationship the employee sought with the employer.…”
Section: Psychological Contractsmentioning
confidence: 99%
“…More specifically, employees who place greater emphasis on the employment relationship itself will be more negatively influenced by the violation than those who do not. Rousseau (1990) identified careerism as an important factor in determining a desired employment relationship. Individuals high on careerism perceive their current employer as an instrumental stepping-stone up the interorganizational career ladder and are likely to adopt a more 'transactional' employment relationship with their employer.…”
Section: Psychological Contract Violation and Its Impactmentioning
confidence: 99%
“…Relational obligations involve socio-emotional resources, such as mutual support and concern between the employer and the employee (Rousseau, 1990). Social and interpersonal concerns dominate in arrangements generating high-commitment employment.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Implicit in this is that they are based on perceived promises (explicit or implicit) made by the employer. When employees believe that the organisation has failed to fulfil obligations contained in the contract, breach occurs (Rousseau, 1990). Previous literature on psychological contracts has employed the sensemaking theory to explain the dynamics of contract breach (Conway and Briner, 2005;Morrison and Robinson, 1997).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%